An evaluation on the contribution of differential mode and common mode currents in radiated emission of digital circuits - Mozi, Aiza Mahyuni (2009)
Electromagnetic Compatibility (EMC) is an issue that has rapidly increased in importance in recent years, driven by legal, and conunercial demands. The EMC compliance requires the implementation of a total EMC approach to the development of electric and electronic circuitry such as in product manufacturing, with compliance being an integral part of the product life-cycle. Radiated emission test is one of the EMC criteria with a purpose to ensure that other products are protected from the emissions generated by it. TIns project is focused on the contribution of Differential Mode Current (Id) and Conunon Mode Current (Ie), that occur in electric and electronic circuitry wmch definitely affects the overall radiated emissions level. A standard test circuit was designed and implemented as the reference circuit. Several of the test circuits were designed and developed using appropriate layout design techniques such as loop area control and appropriate grounding techniques to ensure signal quality and functional performances due to EMC. The value of Id exhibited significantly much mgher values than Ie for frequency ranges between 30 MHz to 1000 MHz throughout all the measurements. Despite the significantly different values between Id and Ie , the total radiated emissions over the frequency ranges exlnbited consistent results. Tms indicate that although the values of Ie were noticeably lower than Id, Ie still dominated the radiated emission in electric and electronic circuitry. The effects of loop area and grounding techniques on radiated emission were also studied. There was a 0.3 % of reduction regarding loop area technique using double-sided PCB compared to the standard test circuit. The average value of radiated emission produced by the test circuit due to Id exhibited a reduction of3.42 % from the standard test circuit, wmle the average value of radiated emission produced by the test circuit due to Ie exhibited a reduction of 2.17 % from the standard test circuit. Future work should focus on improving the circuit design and development using multilayer PCB for optimal performance. Furthermore, effort can also be made on expanding the circuit design by implementing noisy sources such relays and motors, and improve the circuit with higher density and more traces.